Income inequality across provinces in Indonesia: An empirical analysis of human development, economic performance, and labor market conditions - Bina, Al; Optari, Leni Kurnia; Widiya, Heni (Privietlab, 2025)
Income inequality is one of the structural challenges faced by many countries, including Indonesia. This phenomenon reflects an unequal distribution of income across regions, which can lead to social injustice and hinder the process of economic development. This study aims to analyze the effects of the Human Development Index (HDI), economic growth, and unemployment rates on income inequality across 34 provinces in Indonesia over the period 2019–2024. The method employed is panel data regression analysis. The findings reveal that the unemployment rate has a positive and significant effect on income inequality. The HDI shows a significant negative effect, while economic growth does not exhibit a statistically significant impact. These findings highlight the importance of policies that prioritize job creation and human development in addressing inequality. Economic growth strategies should also be designed to be more inclusive.